Hepatocellular Carcinoma in an Infant due to HBV Vertical Transmission - Nunung Ainur Rahmah; Wirasmi Marwoto; Vera Yuwono; Ening Krisnuhoni; Diah Rini Handjari; Darmawan Kartono; David Handojo Muljono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Hepatocellular carcinoma (HCC) is one of the common tumors in the world. The incidence of HCC generally increases with age in all population but there is a tendency of decreasing incidence in the elderly and it is very rare in children. This is a case report of HCC in a 9-month-old boy, who was admitted to the hospital with palpable abdominal mass in the right upper quadrant. Imaging modality by ultrasonography could not adequately demonstrate definite findings demonstrating that the tumor was derived from liver, and the diagnosis was neuroblastoma. Intra-operatively, the tumor mass appeared to be derived from the surface of the posterior edge of the liver, so it was a pedunculated tumor. The histopathological examination revealed a pedunculatedhepatocellular carcinoma grade 3. The Victorian blue staining and immunohistochemical staining were done afterward, which showed HBsAg positive result as found in non-tumor lesion as well as inneoplastic lesion of liver tissue.Keywords: hepatocellular carcinoma, pedunculated HCC, infant HCC, occult hepatitis B virus infection